Resolution regarding the attitude of the government towards the Beveridge Plan (covering letter) - Royal Arsenal (London, England); Glasson, Francis E.
1943-02-19 1943 1940s 2 pages Woolwich Arsenal Shop Stewards' Committee Phone : Woolwich Arsenal 2080 (Extension 989) Secretary F.E. GLASSON. 9, Swanbridge Road, Bexleyheath, Kent. Sir W. Citrine, Secretary, T.U.C. Transport House, Smith Square, Westminster. S.W.1. Date......19th February 1943. Dear Sir, I am instructed to inform you that the enclosed resolution was sent today to the Prime Minister on behalf of the above Committee. Yours fraternally, Francis E. Glasson Secretary. P.C. Noted. 25.3.43 EM. 292/150.5/5/162